4CPS-249 Comparative analysis of anaesthesia report and medication reconciliation in an orthopaedic surgery department. (2nd March 2018) - Henry, C; Roseau, C; Dumenil, AS; Mercier, F; Rieutord, A; Roy, S
Abstract : Background: For 7 years, the orthopaedic surgery department (OSD) has benefited from the Best Possible Medication History (BPMH). The BPMH aim was to assist surgeons in maintaining good prescribing practices. However, they still preferentially used the anaesthesia report (AR) to prescribe. Purpose: The main purpose of this study was to identify unintended medication discrepancies (UMD) between BPMH and AR regarding their type, number and clinical impact. Material and methods: We present a prospective study of 2 months including all hospitalised patients in the OSD and having a BPMH with at least one treatment line. BPMH were performed by a pharmacy student, validated by a pharmacist and recorded in the patient's medical electronic file. BPMH and AR were compared by a resident pharmacist. All discrepancies were classified as undocumented UMD and an anaesthetist assessed their clinical impact: low, moderate or serious. 1 Results: One hundred and two patients were included (age: 72.1±14., 4 years): 52 were admitted for elective surgery and 50 for emergency surgery. Length of stay was 9.5±6.3 days. Thirty two per cent of BPMH were available within 24 hours following patient admission (69% within 48 hours). BPMH reported 701 treatments lines. Only 98 patients had an AR. The comparison between BPMH and AR reported 660 treatment lines in BPMH and 681 lines in AR. Two hundred and sixty UMD have been found concerning 72 patients. We found 152 omissions, 36 posology differences, 29 missed posology, 22 additions and 16 'others'. The therapeutic classes mainly concerned were: nervous system (35%), alimentary tract and metabolism (27%), and cardiovascular system (18%). The clinical impact was low for 60.4% of UMD, moderate for 30% and serious for 9.6%. Of 25 UMD reported as serious, 18 were linked to cardiovascular medicines (72%). Conclusion: This study highlights that medication reconciliation at admission has an important clinical impact in a surgery unit. The AR remains mainly used by the surgeon to establish prescriptions because of his generally earlier availability. However, our results suggest the need to proceed to reengineering the medication reconciliation process to improve the collaboration between pharmacist and anaesthetist. Reference and/or Acknowledgements: 1. Cornish PL, et al. Unintended medication discrepancies at the time of hospital admission. Arch Intern Med2005;165(4):424–429. No conflict of interest